Penerapan Metode Sorongan Dalam Menghafal Al-Quran - Ibnu, Ibnu (Al-Riwayah : Jurnal Kependidikan, 2016)
Sorogan method is a logical consequence of maximum service to the Islamic students (santri). Various efforts of renewal today is done to give to services to students. The sorogan method actually puts maturity and attention as well as the skills of a person. The goal of sorongan method is to direct the students in understanding the subject matter and close relations between students and teachers. In addition, in the sorogan method the teacher can use it to explore the mental turmoil or problems that faced by each student, especially those that could potentially interfere with the absorption of their knowledge. Of course, this method has advantages and disadvantages as well. Therefore, this paper describes the sorogan method, both advantages and disadvantages